2018
DOI: 10.24911/ejmcr/2/11
|View full text |Cite
|
Sign up to set email alerts
|

Delta-9-tetrahydrocannabinol for the treatment of a child with Tourette syndrome: case report

Abstract: Background: Tourette syndrome (TS) is a childhood-onset neuropsychiatric disorder characterized by motor and vocal tics. In severe treatment-resistant cases of TS, cannabis-based medicine could be used alternatively as a therapy of last choice. Case Presentation:We present the case of an 7-year-old boy with severe TS and comorbid attention deficit/hyperactivity disorder (ADHD), who significantly benefitted from treatment with cannabis-based medicine. During an episode with increased tics, he became depressed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
6
0
3
Order By: Relevance
“…Since many patients are dissatisfied with established therapies, they seek for alternative treatments including cannabis-based medications. From open uncontrolled studies [1][2][3][4][5][6][7] and two small randomized controlled trials [8,9], it is suggested that delta-9-tetrahydrocannabinol (THC, dronabinol), the most psychoactive ingredient of cannabis, but also cannabis and the cannabis extract nabiximols are effective in the treatment of tics and psychiatric comorbidities including ADHD, depression, anxiety, rage attacks, and OCD in patients with TS.…”
Section: Introductionmentioning
confidence: 99%
“…Since many patients are dissatisfied with established therapies, they seek for alternative treatments including cannabis-based medications. From open uncontrolled studies [1][2][3][4][5][6][7] and two small randomized controlled trials [8,9], it is suggested that delta-9-tetrahydrocannabinol (THC, dronabinol), the most psychoactive ingredient of cannabis, but also cannabis and the cannabis extract nabiximols are effective in the treatment of tics and psychiatric comorbidities including ADHD, depression, anxiety, rage attacks, and OCD in patients with TS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a substantial number of patients seek for alternative treatments including cannabis-based medicines (CBM). While there is increasing evidence that different CBM might be effective in the treatment of adults with TS [1-4], in minors only two single case reports are available suggesting beneficial effects of orally administered pure delta-9-tetrahydrocannabinol (THC) – the most psychoactive ingredient of cannabis – in 8- and 15-year-old boys with TS and comorbid attention-deficit/hyperactivity disorder [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus wurde über eine erfolgreiche Therapie eines 7-jährigen Jungen mit schwerem GTS berichtet [19]. Nachdem Therapieversuche mit Risperidon, Aripiprazol, Tiaprid, Methylphenidat und Guanfacin nicht zu einer Verbesserung der Tics und der ADHS geführt hatten, verschlechterte sich der Zustand des Jungen und es kam zu einem sozialen Rückzug, Schulverweigerung sowie einer Depression mit Suizidgedanken.…”
Section: Behandlungen Von Kindern Und Jugendlichenunclassified
“…Schließlich findet sich in der Literatur die Schilderung eines 12-jährigen Jungen mit GTS, dessen Eltern -beide ebenfalls Ärzte -eine Behandlung mit inhalativem Medizinalcannabis (0,02 g Sorte Bedrocan ® pro Tag, entsprechend 4,4 mg THC) zur Therapie einer schweren Schlaflosigkeit eingeleitet hatten. Die Eltern und der Junge berichteten nicht nur über eine Verbesserung des Schlafs, sondern auch der Tics und des vorangehenden Dranggefühls [19].…”
Section: Behandlungen Von Kindern Und Jugendlichenunclassified
See 1 more Smart Citation